The diachrony of classification systems - McGregor, William, 1952-; Wichmann, Søren, 1964- (Amsterdam studies in the theory and history of linguistic science. Current issues in linguistic theory ;, 2018)
Some papers presented at a conference held at the Netherlands Institute for Advanced Studies in the Humanities and Social Sciences, Wassenaar, The Netherlands on 12-3 March, 2009.